Diversifikasi Produk Tempe melalui Penerapan Teknologi Tepat Guna untuk Industri Rumah Tangga: Product Diversification of Tempe through the Application of Appropriate Technology for Household Industries - Saefudin, Slamet; Pujianto, M. Edi; Puspita, Nurul; Rohman, Taufik (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Tempe is a traditional Indonesian food with high nutritional value, particularly in its plant-based protein content. However, its market value remains relatively low when sold only in fresh form due to its limited shelf life, fluctuating raw material prices, and the lack of innovation in derivative products. This community service program was carried out to support the diversification of tempe products by applying appropriate technology for Tempe Jowo Household Industry (IRT), the partner. The implementation methods included problem observation, socialization, and training, as well as the application of technology through a slicing machine, an oil spinner, and a hand sealer for packaging. The results showed a significant increase in the partner's knowledge and skills, with the average post-test score rising from 60 to 82. More than 80% of participants were able to properly practice the production techniques for tempe chips, including slicing, temperature-controlled frying, and hygienic packaging. The application of appropriate technology improved production efficiency, reducing processing time by 30–40% compared to manual methods. The resulting tempe chips had a crunchier texture, better flavor, a longer shelf life, and more hygienic, attractive packaging. With product innovation and technological support, the partner IRT enhanced competitiveness and expanded market opportunities for modern retail and online platforms.